2023
DOI: 10.1088/1361-6633/ad14f3
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase transitions in two-dimensional superconductors: a review on recent experimental progress

Ziqiao Wang,
Yi Liu,
Chengcheng Ji
et al.

Abstract: Superconductor–insulator/metal transition (SMT) as a paradigm of quantum phase transition has been a research highlight over the last three decades. Benefit from recent developments in the fabrication and measurements of two-dimensional (2D) superconducting films and nanodevices, unprecedented quantum phenomena have been revealed in the quantum phase transitions of 2D superconductors. In this review, we introduce the recent progress on quantum phase transitions in 2D superconductors, focusing on the quantum Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 200 publications
0
7
0
Order By: Relevance
“…For most previous reports of SIT/SMT, there exists a single QCP with a single value of zν during the transition. 6 However, the previous consensus has been challenged by the discovery of the quantum Griffiths singularity (QGS), which was first observed in three-monolayer (3-ML) Ga films on GaN (0001) substrate. The ultrathin (2-ML) Ga films grown by MBE exhibit graphene or silicene-like structure, differing from the bulk counterparts with orthorhombic (α and γ phase) or monoclinic (β phase) structures.…”
Section: ■ Quantum Griffiths Singularitymentioning
confidence: 99%
See 3 more Smart Citations
“…For most previous reports of SIT/SMT, there exists a single QCP with a single value of zν during the transition. 6 However, the previous consensus has been challenged by the discovery of the quantum Griffiths singularity (QGS), which was first observed in three-monolayer (3-ML) Ga films on GaN (0001) substrate. The ultrathin (2-ML) Ga films grown by MBE exhibit graphene or silicene-like structure, differing from the bulk counterparts with orthorhombic (α and γ phase) or monoclinic (β phase) structures.…”
Section: ■ Quantum Griffiths Singularitymentioning
confidence: 99%
“…The nature of the anomalous metallic state is beyond the fundamental understanding of superconductivity and, thus, has become one of the major open issues in condensed matter physics. 6,10 Nevertheless, the early experimental observations of the anomalous metallic state are questioned by the possible extrinsic effects like electromagnetic noise, 23−25 casting doubt on the existence of the anomalous metallic state.…”
Section: ■ Anomalous Metallic Statementioning
confidence: 99%
See 2 more Smart Citations
“…Quantum phase transition (QPT) in two-dimensional (2D) superconducting systems, such as ultrathin films and heterogeneous interfaces, is an important topic for the deep understanding of quantum states, where the ground state is changed at absolute zero temperature in response to a variation of external parameter of the Hamiltonian . Superconductor–insulator/metal transition (SIT/SMT) as a prototype of QPT has been extensively studied, and numerous experiments have been performed by tuning magnetic field, disorder, or charge density, which greatly enriches the physical characteristics of QPT around the quantum critical points. One of the most striking phenomena is the quantum Griffiths singularity (QGS) with the signature of divergent dynamic critical exponent approaching zero temperature, instead of a constant critical exponent or finite saturated values in conventional QPT. A number of experiments have verified the existence of QGS near the quantum critical points of SIT/SMT in 2D superconducting systems, such as three-monolayer crystalline superconducting Ga film, LaAlO 3 /SrTiO 3 (110) interface, monolayer NbSe 2 , ion-gated crystalline ZrNCl and MoS 2 . Theoretically, the QGS behavior has been attributed to the emergence of rare superconducting puddles resulting from disorder-induced vortex glass-like phase. , However, it has been found that the in-plane QGS phase also exists in 2D crystalline PdTe 2 films and highly disordered β-W films without vortex formation, revealing a novel microscopic nature of the origination of QGS.…”
mentioning
confidence: 99%